Tinjauan Naratif Transformasi Digital dalam Manajemen Rumah Sakit di Indonesia Periode Tahun 2020-2025 - Gemilang Mutsaqqofa Arsyadana; Tjatur Prijambodo (Universitas Muhamadiyah Manado, 2026)
In order to raise the standard of healthcare services in the contemporary period, digital transformation in hospital management has become a phenomena. The purpose of this study is to investigate the adoption, advantages, difficulties, and success aspects of digital transformation in healthcare facilities. A literature review employing a narrative review system was the methodology. 14 papers that met the inclusion requirements were found using data sources from Google Scholar, PubMed, and ScienceDirect databases with publication years ranging from 2020 to 2025. To determine the primary study themes, data analysis was carried out utilising a thematic synthesis approach. According to the study's findings, digital transformation can enhance operational effectiveness, service quality, and patient safety by using technology including electronic health records (EHR), telemedicine, and hospital management information systems. However, there are still a number of obstacles to its adoption, such as inadequate infrastructure, inadequate human resource competency, expensive investment costs, and data security threats. Significant barriers also include a lack of system integration and opposition to change. Government policies and regulatory assistance have an impact on the success of digital transformation in hospital administration.